Windfalls and Consumption Under a Borrowing Constraint - Wiseman, Clark (The Review of Economics and Statistics, 1975)
The emphasis here is on a micro-economic derivation of the theoretical propensity to consume windfalls under limited borrowing capacity. This is done in the next section by means of a comparative static analysis employing a reduced intertemporal utility function. The final section reports a test whose results conform to the prediction of the analysis that the propensity to consume windfalls is negatively related to size of the windfall.